2020
DOI: 10.1101/2020.04.01.018481
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Succinct Dynamic de Bruijn Graphs

Abstract: Motivation:The de Bruijn graph is one of the fundamental data structures for analysis of high throughput sequencing data. In order to be applicable to population-scale studies, it is essential to build and store the graph in a space-and time-efficient manner. In addition, due to the ever-changing nature of population studies, it has become essential to update the graph after construction e.g. add and remove nodes and edges. Although there has been substantial effort on making the construction and storage of th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 29 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…Second, a graph can be directly updated if it is represented using dynamic data structures (e.g., SuccinctDBG in the dynamic form), which support dynamic updates. This approach allows making instant changes, however, does not enable large updates because of the limited performance of dynamic data structures [2]. Finally, for large updates, the existing index can be completely reconstructed.…”
Section: Methodsmentioning
confidence: 99%
“…Second, a graph can be directly updated if it is represented using dynamic data structures (e.g., SuccinctDBG in the dynamic form), which support dynamic updates. This approach allows making instant changes, however, does not enable large updates because of the limited performance of dynamic data structures [2]. Finally, for large updates, the existing index can be completely reconstructed.…”
Section: Methodsmentioning
confidence: 99%
“…Here, we give some background on this modification. Alipanahi et al (2020a) observed that FDBG fails for datasets approaching 2 32 distinct nodemers. This is due to hash collisions.…”
Section: Implementation Of Fdbg-recsplitmentioning
confidence: 98%
“…Munro et al also explained how their ideas could be used to obtain dynamic compact representations of graphs, and Coimbra et al (2020) recently applied those ideas to obtain an implementation of dynamic k 2 -trees that is competitive with previous implementations, which were essentially just static k 2 -trees but with dynamic instead of static bitvectors. Since Dynamic-BOSS (Alipanahi et al, 2020a) is essentially the data structure of Bowe et al (2012) but with dynamic instead of static bit vectors, we are naturally curious how competitive a dynamic de Bruijn graph based on Munro et al's ideas will be.…”
Section: Dynamizing Compact Data Structuresmentioning
confidence: 99%
See 2 more Smart Citations